The Effects of Land Use and Land Cover Changes on the Land Surface Temperature Over Northeast China - Guanghui Yuan; Ran Ding; Yubao Liu; Lei Zhang; Haixiang Xu (Advances in Meteorology)
To investigate the impacts of land use and land cover change (LULCC) on regional climate in Northeast China, the weather research and forecasting (WRF) model was run with the satellite land cover type, vegetation fraction (Fg), leaf area index, and albedo in 2001 and 2018, respectively, and the results were compared. The major LULCC during 2001–2018 were conversions from grasslands to croplands over the central regions of Northeast China and conversions from woody savannas to deciduous broadleaf forests in the northern and eastern portions of Northeast China. The changes in Fg and albedo are highly correlated with the daytime land surface temperature (Ts). From 2001 to 2018, the daytime Ts is decreased (increased) over the central regions of Northeast China by more than 1 K in summer (winter). There is also a widespread, about 1 K, cooling in the spring and autumn temperatures. The changes of the nighttime Ts and the daytime Ts from 2001 to 2018 are similar in summer, autumn, and winter, but the nighttime Ts changes are comparatively smaller. Analysis of the surface energy budget and the biophysical effects found that the cooling of the daytime Ts over the central regions of Northeast China in spring, summer, and autumn from 2001 to 2018 can be attributed to a decrease of absorbed shortwave radiation and an increase of latent heat flux corresponding to LULCC. This cooling is weakened by the decrease of the sensible heat flux. In contrast, the widespread warming trend of the daytime Ts in winter is mainly due to an increased net shortwave radiation, which offsets the cooling effects of surface fluxes. During the nighttime, the soil heat flux contributes the most to the changes of Ts.